2012
DOI: 10.5604/17322693.1000980
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IL18 gene polymorphisms on mRNA levels and interleukin-18 release by peripheral blood mononuclear cells

Abstract: Our study supports the role of rs1946518 (-607A>C) and rs187238 (-137G>C) SNPs as genetic determinants of the observed variability in IL18 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The association of two functional polymorphisms in the IL‐18 promoter, −607C/A (rs1946518) and −137G/C (rs187238), with the risk of BD was investigated previously in different populations. Our results showed similar association concerning the −607 (C/A) SNP in the Korean population where BD patients had a significantly higher frequency of the −607 C allele (60.7% vs. 48.1%, OR 1.668, 95% CI 1.129–2.464, P = 0.0101) . On contrary, opposite results were observed in the Turkish population, where a genetic association between allele ‘A’ in rs1946518 (−607 C/A) and BD (39% vs. 19%, OR = 1.48, 95% CI = 1.10–1.97, P = 0.0088) was detected .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The association of two functional polymorphisms in the IL‐18 promoter, −607C/A (rs1946518) and −137G/C (rs187238), with the risk of BD was investigated previously in different populations. Our results showed similar association concerning the −607 (C/A) SNP in the Korean population where BD patients had a significantly higher frequency of the −607 C allele (60.7% vs. 48.1%, OR 1.668, 95% CI 1.129–2.464, P = 0.0101) . On contrary, opposite results were observed in the Turkish population, where a genetic association between allele ‘A’ in rs1946518 (−607 C/A) and BD (39% vs. 19%, OR = 1.48, 95% CI = 1.10–1.97, P = 0.0088) was detected .…”
Section: Discussionsupporting
confidence: 76%
“…IL-18 gene is located on chromosome 11q22. 2-22.3 (18), and several polymorphisms within IL-18 promoter gene have been associated with different inflammatory and autoimmune diseases (19)(20)(21)(22)(23). In addition, many investigators identified a significant higher frequency of À137 GG and the CC À607 genotypes in BD patients in comparison with controls (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that IL18 promoter gene polymorphisms rs187238 and rs1946518, may influence promoter activity and IL18 production [12,16,17]. Previous studies have indicated that IL16 and IL18 are pro-inflammatory cytokines involved in the pathogenesis of diabetes [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies www. journals.viamedica.pl/ginekologia_polska have revealed that cytokine production may be associated with polymorphisms in cytokine-encoding genes [12]. These polymorphisms may alter gene expression and cytokine synthesis, and have been investigated in patients with type 1 and type 2 diabetes [13].…”
Section: Introductionmentioning
confidence: 99%
“…For position −137, a change from nucleotide G to nucleotide C affects the H4TF-1 nuclear factor binding site, which may confer a higher IL-18 protein expression [32]. Furthermore, a recent study reported by Dziedziejko et al [33] also found rs1946518 (−607A/C) AA homozygotes showed significantly lower IL-18 release and mRNA expression after stimulation(stimulants: PHA, LPS, and anti-CD3/CD28 antibodies),and as well as rs187238 (−137G/C) C allele after PHA treatment. These observations support our study, in which IL-18 rs1946518 C allele was associated with high IL-18 production, and high levels of IL-18 were associated with RA and SLE [8,9], so IL-18 rs1946518 A allele might have a protective effect on RA and SLE.…”
Section: Discussionmentioning
confidence: 99%